Medical treatment or surgery for colorectal endometriosis? Results of a shared decision-making approach. Issue 2 (8th December 2017) - Vercellini, Paolo; Frattaruolo, Maria Pina; Rosati, Riccardo; Dridi, Dhouha; Roberto, Anna; Mosconi, Paola; De Giorgi, Olga; Cribiù, Fulvia Milena; Somigliana, Edgardo
Abstract: STUDY QUESTION: What is the degree of patient satisfaction in women with symptomatic colorectal endometriosis who choose medical or surgical treatment after a shared decision-making (SDM) process? SUMMARY ANSWER: The degree of satisfaction with treatment was high both in women who chose medical treatment with a low-dose oral contraceptive (OCP) or a progestin, and in those who chose to undergo surgical resection of bowel endometriosis. WHAT IS KNOWN ALREADY: Hormonal therapies and surgery for colorectal endometriosis have been investigated in non-comparative studies with inconsistent results. STUDY DESIGN, SIZE, DURATION: Parallel cohort study conducted on 87 women referring to our centre with an indication to surgery for colorectal endometriosis. A standardised SDM process was adopted, allowing women to choose their preferred treatment. Median follow-up was 40 [18–60] months in the medical therapy group and 45 [30–67] in the surgery group. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients with endometriosis infiltrating the proximal rectum, the rectosigmoid junction, and the sigmoid, not causing severe sub-occlusive symptoms were enroled. A total of 50 patients chose treatment with an OCP ( n = 12) or a progestin ( n = 38), whereas 37 women confirmed their previous indication to surgery. Patient satisfaction was graded according to a 5-category scale. Variations in bowel and pain symptoms were measured by means of a 0–10 numeric rating scale. Constipation was assessed with the Knowles–Eccersley–Scott Symptom Questionnaire (KESS), health-related quality of life with the Short Form-12 questionnaire (SF-12), psychological status with the Hospital Anxiety and Depression scale (HADS) and sexual functioning with the Female Sexual Function Index (FSFI). MAIN RESULTS AND THE ROLE OF CHANCE: Six women in the medical therapy group requested surgery because of drug inefficacy ( n = 3) or intolerance ( n = 3). Seven major complications were observed in the surgery group (19%). At 12-month follow-up, 39 (78%) women in the medical therapy group were satisfied with their treatment, compared with 28 (76%) in the surgery group (adjusted odds ratio (OR), 1.37; 95% confidence interval (CI), 0.45–4.15; intention-to-treat analysis). Corresponding figures at final follow-up assessment were 72% in the former group and 65% in the latter one (adjusted OR, 1.74; 95% CI, 0.62–4.85). The 60-month cumulative proportion of dissatisfaction-free participants was 71% in the medical therapy group compared with 61% in the surgery group ( P = 0.61); the Hazard incidence rate ratio was 1.21 (95% CI, 0.57–2.62). Intestinal complaints were ameliorated by both treatments. Significant between-group differences in favour of medical treatment were observed at 12-month follow-up in diarrhoea, dysmenorrhoea, non-menstrual pelvic pain and SF-12 physical component scores. The total HADS score improved significantly in both groups, whereas the total FSFI score improved only in women who chose medical therapy. LIMITATIONS REASONS FOR CAUTION: As treatments were not randomly assigned, selection bias and confounding are likely. The small sample size exposes to the risk of type II errors. WIDER IMPLICATIONS OF THE FINDINGS: When adequately informed and empowered through a SDM process, most patients with non-occlusive colorectal endometriosis who had already received a surgical indication, preferred medical therapy. The possibility of choosing the preferred treatment may allow maximisation of the potential effect of the interventions. STUDY FUNDING/COMPETING INTEREST(S): This study was financed by Italian fiscal contribution '5 × 1000'—Ministero dell'Istruzione, dell'Università e della Ricerca—devolved to Fondazione Istituto di Ricovero e Cura a Carattere Scientifico Ca' Granda Ospedale Maggiore Policlinico, Milano, Italy. P.V., M.P.F., R.R., D.D., A.R., P.M., O.D.G. and M.C. declare that they have no conflicts of interest. E.S. received grants from Ferring and Serono.